Characterization and utilization of self-assembled diphenylalanine nanotubes - Xu, Kairuo (2011)
Diphenylalanine (FF) peptide is the core-recognition motif of β-amyloid polypeptide, a peptide associated with diseases such as Alzheimer’s and which is known to be capable of self-assembly. FF has attracted interest in nanotechnology due to the physical and chemical stability and mechanical rigidity of the self-assembled nanotube form of the peptide. A number of promising applications of FF nanotubes have previously been explored. To extend this work to biomedical and pharmaceutical areas, an improved understanding of the physicochemical properties of FF tubes, together with the influence of assembly conditions, cytotoxicity properties and potential in drug delivery field are presented in this thesis.